Development of a psychological training program for conflict management at the enterprise «Vidpochinok na vsi sto» - Irina Shamara; Julia Kurdiukova (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2024)
In order to improve the efficiency of tourism enterprises, it is important to use modern approaches to conflict management that take into account the psychological aspects of interaction in the team. Conflicts that arise in this area can significantly affect the quality of services, the level of customer satisfaction and the internal climate of the organization. Therefore, special attention should be paid to methods of their prevention and resolution. The study analyzes the nature of conflicts in tourism enterprises, the main factors that determine them, and considers the possibilities of reducing their negative impact on the activities of the organization.The emphasis is on the application of psychological methods, such as the development of active listening skills, improving stress management strategies and creating a positive communication environment. The issue of resolving conflicts through mediation and coaching, which allows minimizing their escalation, is considered. The study is based on an integrated approach using the methods of system analysis, questionnaires, structural modeling and the descriptive method. As a result, practical recommendations were proposed for improving management decisions aimed at creating a favorable socio-psychological climate in the team and ensuring the stable development of the enterprise. The subject of the study is the psychological aspects of conflict management at the tourist enterprise «Vidpochinok na vsi sto». The purpose of the study is to develop measures to improve conflict management at the enterprise «Vidpochinok na vsi sto». General scientific research methods are used: systemic, descriptive, comparative and structural-logical analysis. The following results were obtained during the study: the psychological climate was analyzed and the main causes of conflict situations at the enterprise «Vidpochinok na vsi sto» were identified. Conclusions: the feasibility of developing a psychological training program to improve conflict management at the enterprise «Vidpochinok na vsi sto» is substantiated and the expected results of conducting a conflict management training program at the enterprise are determined.